The multistage Adomian Decomposition Method for solving chaotic Lü System - Razali, Nur Isnida; Chowdhury, Md. Sazzad Hossien; Asrar, Waqar (IDOSI Publications, 2013)
In this paper, a numerical scheme based on adaption of standard Adomian Decomposition Method (ADM) is applied to the chaotic Lü system. Then, the standard ADM is converted into a hybrid numeric-analytic method called the multistage ADM (MADM). Numerical comparisons with the standard ADM and the fourth-order Runge-Kutta method (RK4) is made in order to prove that MADM is the reliable method for nonlinear problems.